Prospects of anti-HIV therapy and prophylaxis - De Clercq, Erik (Henry Stewart Talks, 2011)
Targets for anti-HIV therapy, Reverse transcriptase, Nucleoside reverse transcriptase inhibitors, Nucleotide reverse transcriptase inhibitors, Non-nucleoside reverse transcriptase inhibitors, Protease inhibitors, Fusion inhibitors, Co-receptor inhibitors, Integrase inhibitors, Anti-HIV drug combinations, Prophylaxis of HIV infections